Real-time communication in unconstrained shared ethernet networks: The virtual token-passing approach - Francisco Carreiro (2005)
Traditional shared Ethernet networks have a non-deterministic behaviour, which impairs the support of real-time communication. In this paper, it is proposed a shared Ethernet deterministic architecture, able to interconnect sensors, controllers and actuators at the field level, allowing the coexistence of standard devices with enhanced (real-time). devices. Such solution is based on the control of the medium access right, by means of a virtual token passing procedure among enhanced stations, complemented by an underlying prioritization mechanism. Such underlying mechanism guarantees that, whenever an enhanced (real-time) station is contending for the bus access, it will be able to access the bus prior to any other station. Thus, it enables the traffic separation between standard and enhanced (real-time) stations, being able to guarantee real-time communication in unconstrained traffic environments.